A multi-level and multi-actor approach to risk governance: a conceptual framework to support policy development for Ambrosia weed control - Oude Lansink, Alfons G.; Schut, Marc; Kamanda, J.; Klerkx, Laurens (Informa UK Limited, 2018)
Invasive species such as Ambrosia (an annual weed) pose a biosecurity risk whose management depends on the knowledge, attitudes and practices of many stakeholders. It can therefore be considered a complex policy and risk governance problem. Complex policy problems are characterised by high uncertainty, multiple dimensions, interactions across different spatial and policy levels, and the involvement of a multitude of actors and organisations. This paper provides a conceptual framework for analysing the multi-level and multi-actor dimensions of Ambrosia management. Potential and existing public, private and public–private management strategies are identified to address the interests and needs of different actor groups across different levels. We conclude that policies that promote a mix of public and private Ambrosia management strategies may respond better to the needs and interests of different actor groups across different levels than a one-size-fits-all approach. However, multiple policy strategies need to be aligned in order to lead to synergies and spreading coherent messages to the public. Collaboration may enhance the likelihood of biosecurity management and risk governance of Ambrosia being adequately implemented and enforced.